Utilising Grape Pomace for Ethanol Production - Korkie, L.J.; Janse, B.J.H.; Viljoen-Bloom, M. (South African Journal of Enology and Viticulture, 2017)
Chemical analyses of grape pomace revealed the presence of significant amounts of fermentable sugars that are retained in the pomace after pressing of the grapes. Furthermore, treatment of the pomace with purified hydrolases indicated that the enzymatic biodegradation of the pomace could release additional fermentable sugars. We isolated and evaluated yeast strains associated with grape pomace for their ability to hydrolyse the complex polysaccharides found in grape pomace and to utilise the fermentable sugars for the production of ethanol. Two Pichia rhodanensis isolates were able to partially hydrolyse the pomace polysaccharides, but fermentation of the pomace resulted only in a small increase in the amount of ethanol produced. The study revealed that significant amounts of ethanol could be obtained from the residual sugars associated with grape pomace. However, the complex structure of the pomace polysaccharides apparently renders it unsusceptible to efficient hydrolysis under fermentative conditions.